Physiological and Selective Attention Demands during an International Rally Motor Sport Event. (19th March 2015) - Turner, Anthony P.; Richards, Hugh
Abstract : Purpose . To monitor physiological and attention responses of drivers and codrivers during a World Rally Championship (WRC) event. Methods . Observational data were collected from ten male drivers/codrivers on heart rate (HR), core body (T core ) and skin temperature (T sk ), hydration status (urine osmolality), fluid intake (self-report), and visual and auditory selective attention (performance tests). Measures were taken pre-, mid-, and postcompetition day and also during the precompetition reconnaissance. Results . In ambient temperatures of 20.1°C (in-car peak 33.9°C) mean (SD) peak HR and T core were significantly elevated (P < 0.05 ) during rally compared to reconnaissance (166 (17) versus 111 (16) beats·min −1 and 38.5 (0.4) versus 37.6 (0.2)°C, resp.). Values during competitive stages were substantially higher in drivers. High urine osmolality was indicated in some drivers within competition. Attention was maintained during the event but was significantly lower prerally, though with considerable individual variation. Conclusions . Environmental and physical demands during rally competition produced significant physiological responses. Challenges to thermoregulation, hydration status, and cognitive function need to be addressed to minimise potentially negative effects on performance and safety.